The Voigt profile expressed as a linear sum of a Gaussian and a Lorentzian functions, when the weight depends on the widths ratio and the independent variable - Di Rocco, Hector Omar (2012)
Using one of the differential equation that V(x) satisfies, at the present paper we obtain m(a,x) as a function, not only of a, but also of x. Kielkopf first propose m(a,x) based on numerical arguments. We find that,the Voigt function calculated with the expression m(a,x) we have obtained in this paper, deviates from the exact value less than m(a) does, specially for high |x| values.